2017
DOI: 10.1002/qj.3021
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale orographic gravity wave drag in stable boundary layers and its impact on synoptic systems and near‐surface meteorology

Abstract: At present atmospheric models for weather and climate use enhanced turbulent drag under stable conditions, because these empirically provide the necessary momentum drag for accurate forecast of synoptic systems. The enhanced mixing (also known as the ‘long tail’), introduces drag that cannot be physically justified and degrades the score for near‐surface temperature, wind and boundary‐layer height, and degrades fog and frost forecasting. This study hypothesizes that the insufficient representation of small‐sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…In the SBL, IGW may transport momentum between small-scale terrain and the lowermost critical level [195]. The related wave drag can be of the same amplitude of, or even larger than, the turbulent drag [196][197][198]; it has a significant impact on the SBL dynamics, but it can also affect larger scales of motion [199].…”
Section: The Role Of Gravity Wavesmentioning
confidence: 99%
“…In the SBL, IGW may transport momentum between small-scale terrain and the lowermost critical level [195]. The related wave drag can be of the same amplitude of, or even larger than, the turbulent drag [196][197][198]; it has a significant impact on the SBL dynamics, but it can also affect larger scales of motion [199].…”
Section: The Role Of Gravity Wavesmentioning
confidence: 99%
“…For this reason, there is some debate on which source of low‐level mountain drag should be better represented, the results in Tsiringakis et al . () suggesting that trapped lee waves could contribute as much as blocked‐flow mountain drag (Lott and Miller, ) or turbulent subgrid‐scale orographic drag (Beljaars et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Tsiringakis et al . () showed that this additional drag can be provided by accounting for the gravity‐wave drag generated in stable conditions by small‐scale orography. This indicates that an accurate representation of small‐scale drag generation is important for simulations of the large‐scale circulation and thus for the conservation of AAM in models.…”
Section: Discussionmentioning
confidence: 96%
“…Studying the contributions of the different torques to the residuals in more detail in further research may provide directions for further model improvement (Madden and Speth, 1995;Huang et al, 1999). Inaccuracies in the torques can be related to uncertainty in the representation of surface drag in stable conditions (Sandu et al, 2013;Tsiringakis et al, 2017). Sandu et al (2013) demonstrated that, in numerical weather prediction models, increasing the turbulent diffusion in stable boundary layers artificially is necessary to simulate the large-scale atmospheric circulation accurately.…”
Section: Aam Balancementioning
confidence: 99%
See 1 more Smart Citation